TERRITÓRIO, AGROQUÍMICOS E PROCESSO SAÚDE-DOENÇA: ESTUDO DA RELAÇÃO ENTRE O USO DE AGROTÓXICOS NA PRODUÇÃO AGRÍCOLA E OS CASOS DE SUICÍDIO NA POPULAÇÃO RESIDENTE NO TERRITÓRIO BRASILEIRO (2014 – 2024) (CIPEEX, 2026)
Introduction: Pesticides, although essential to agriculture, have had serious social, environmental, and public health impacts. In Brazil, their intensive use has been studied in acute, subacute, and chronic poisonings. Furthermore, easy access to pesticides favors their use in suicides, especially in rural areas, where socioeconomic and cultural factors, as well as a lack of mental health support, intensify this situation. Objective: This article aimed to analyze the relationship between pesticide use and suicide in Brazil, highlighting risk factors, prevalence, and prevention measures. Method: This is an exploratory and descriptive study, based on databases such as PUBMED, SciELO, Web of Science, Lilacs, and Google Scholar. English descriptors related to "Agrochemicals," "Suicide," and "Brazil" were used, combined using logical operators. Results: The analyzed articles demonstrated a higher risk in rural areas, with a higher prevalence among men between 30 and 49 years old, although women presented more non-lethal poisonings. Occupational exposure and social vulnerability were relevant factors. Organophosphates and carbamates, such as "chumbinho," were the substances most associated with the cases. A link was also demonstrated between prolonged exposure, mental disorders, and a higher prevalence of suicidal ideation. Conclusion: The study concludes that exposure to pesticides is strongly associated with increased suicide rates, especially among rural workers, aggravated by socioeconomic and mental health factors. This reinforces the need for public policies for regulation, education, and psychological support to reduce this impact on public health.
Keywords: Agrochemical; Suicide; Brazil